Predictors and Correlates of Depression in Retired Elite Level Rugby League Players - Iverson, Grant L.; Van Patten, Ryan; Terry, Douglas P.; Levi, Christopher R.; Gardner, Andrew J. (Frontiers in Neurology, 2021)
Background: There is considerable interest in determining whether later-in-life depression is associated with lifetime history of concussions or the duration of a career in professional contact and collision sports. Rugby league is a high-intensity collision sport involving a large number of tackles per game and a high rate of concussions. We examined predictors and correlates of depression in retired elite level rugby league players in Australia. Methods: Retired elite level rugby league players (N=141, age: M=52.6, SD=13.8; Range=30-89 years) completed the Depression, Anxiety, and Stress Scale (DASS), Brief Pain Inventory, Connor-Davidson Resilience Scale (CD-RISC), and Epworth Sleepiness Scale; they also reported on lifetime history of concussions. The DASS depression score was regressed on age, total number of self-reported concussions, years played professionally, CD-RISC score, BPI pain interference score, and ESS score. Results: The retired players reported a median of 15 total lifetime concussions [interquartile range (IQR)=6-30], and a median of 8 years playing professional sports (IQR=3.5-11). The proportion of the sample endorsing at least mild current depression was 29%. The DASS depression score was positively correlated with the DASS anxiety (r=.54) and DASS stress scores (r=.58). The CD-RISC score was negatively correlated with the depression score (r=-.53). Depression scores were not significantly correlated with pain severity (r=.14), and were weakly correlated with life interference due to pain (r=.20) and years playing professional sports (r=-.17). Depression scores were not significantly correlated with lifetime history of concussions (r=.14). A multiple regression model, with age, total number of self-reported concussions, years played professionally, the CD-RISC, Brief Pain Inventory-pain interference score, and Epworth Sleepiness Scale score as predictors was significant, with 35% of the variance in DASS depression accounted for. The two significant independent predictors of depression were lower resilience and greater life interference due to pain. Conclusions: This is the first large study of depression in retired rugby league players. Depression in these retired players was not meaningfully associated with lifetime history of concussions or number of years playing elite level collision sport. Depression was associated with current anxiety, stress, resilience, and life interference due to chronic pain.